Comparative Genomics of Sibling Species of Fonsecaea Associated with Human Chromoblastomycosis - Vicente, Vania A.; Weiss, Vinícius A.; Bombassaro, Amanda; Moreno, Leandro F.; Costa, Flávia F.; Raittz, Roberto T.; Leão, Aniele C.; Gomes, Renata R.; Bocca, Anamelia L.; Fornari, Gheniffer; de Castro, Raffael J. A.; Sun, Jiufeng; et al. (Frontiers in Microbiology, 2017)
Fonsecaea and Cladophialophora are genera of black yeast-like fungi harboring agents of a mutilating implantation disease in humans, along with strictly environmental species. The current hypothesis suggests that those species reside in somewhat adverse microhabitats, and pathogenic siblings share virulence factors enabling survival in mammal tissue after coincidental inoculation driven by pathogenic adaptation. A comparative genomic analysis of environmental and pathogenic siblings of Fonsecaea and Cladophialophora was undertaken, including de novo assembly of F. erecta from plant material. The genome size of Fonsecaea species varied between 33.39 and 35.23 Mb, and the core genomes of those species comprises almost 70% of the genes. Expansions of protein domains such as glyoxalases and peptidases suggested ability for pathogenicity in clinical agents, while the use of nitrogen and degradation of phenolic compounds was enriched in environmental species. The similarity of carbohydrate-active versus protein-degrading enzymes associated with the occurrence of virulence factors suggested a general tolerance to extreme conditions, which might explain the opportunistic tendency of Fonsecaea sibling species. Virulence was tested in the Galleria mellonella model and immunological assays were performed in order to support this hypothesis. Larvae infected by environmental F. erecta had a lower survival. Fungal macrophage murine co-culture showed that F. erecta induced high levels of TNF-α contributing to macrophage activation that could increase the ability to control intracellular fungal growth although hyphal death were not observed, suggesting a higher level of extremotolerance of environmental species.